The myth of pure perception. (2016) - Clore, Gerald L.; Proffitt, Dennis R.
Abstract: Firestone & Scholl (F&S) assume that pure perception is unaffected by cognition. This assumption is untenable for definitional, anatomical, and empirical reasons. They discount research showing nonoptical influences on visual perception, pointing out possible methodological "pitfalls." Results generated in multiple labs are immune to these "pitfalls, " suggesting that perceptions of physical layout do indeed reflect bioenergetic resources.